2019
DOI: 10.1016/j.mce.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to the resistance of the thyrocyte to hydrogen peroxide

Abstract: We studied the mechanism that may explain the relative resistance of thyrocytes to H 2 O 2 compared to other cell types. Ability to degrade H 2 O 2 , glutathione peroxidase (GPx) activity, heme oxygenase-1 (HO-1) expression, cell survival and capacity to repair DNA damage after H 2 O 2 exposure or irradiation were measured in human thyrocytes in primary culture and compared to the values obtained in human T-cells and different cell lines. Compared to other cell types, thyrocytes presented a low mortality rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Hydrogen peroxide is relatively stable and can freely diffuse through cellular membranes or via channels like aquaporins 3 and 9 [39,40]. We have previously shown that exogenous H 2 O 2 can induce DNA single and double strand breaks in human thyrocytes [30,33,41]. Recently, it has been shown that irradiation of a human thyroid cell line induces Duox1-dependent H 2 O 2 production provoking persistent DNA damage [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide is relatively stable and can freely diffuse through cellular membranes or via channels like aquaporins 3 and 9 [39,40]. We have previously shown that exogenous H 2 O 2 can induce DNA single and double strand breaks in human thyrocytes [30,33,41]. Recently, it has been shown that irradiation of a human thyroid cell line induces Duox1-dependent H 2 O 2 production provoking persistent DNA damage [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the HEK293 cells are not thyrocytes, which are particularly protected against H 2 O 2 -induced DNA damage. Multiple factors contributing to the resistance of thyrocytes to hydrogen peroxide have been identified [41]. On the contrary, the HEK293 cells are known to be particularly sensitive to the toxic effects of H 2 O 2 [42].…”
Section: Discussionmentioning
confidence: 99%
“…Very strong antioxidant systems are also present in the thyroid cell, which explains that the thyroid cells survive better than other cells after radiation or exposure to ROS and even proliferate if the DNA damages leads to oncogene activation or inactivation of tumor suppressor genes [ 86 , 87 ]. A decrease in some components of the antioxidant system, namely glutathione peroxidase and thioredoxin reductase, has been shown in thyroid cancer (albeit unfortunately without precision on the proportion of women in the population studied) [ 88 ].…”
Section: What Are the Possible Explanations For The Female Predominance?mentioning
confidence: 99%
“…However, in this case, it is necessary to choose suitable culture conditions that could support long-term functional activity of follicular cells, including the optimal concentration of TSH, iodide salts, and growth factors. In addition, considering the activity of peroxidases ( 10 ), it is necessary to provide a balance of factors that control the formation of superoxide radicals. An important requirement for maintaining the polarity (apical localization of microvilli, presence of basal lamina, etc.)…”
Section: Introductionmentioning
confidence: 99%